All-fiber delivery of 100 W single-frequency laser through 100 m anti-resonant hollow-core fiber without stimulated Brillouin scattering - Shoufei Gao; Wenxiang Zha; Yujun Feng; Zhixi Liang; Yizhi Sun; Xiaobo Yang; Yingying Wang (High Power Laser Science and Engineering)
The flexible delivery of single-frequency lasers is far more challenging than that of conventional lasers due to the onset of stimulated Brillouin scattering (SBS). Here we present the successful delivery of 100 W single-frequency laser power through 100 m of anti-resonant hollow-core fiber (AR-HCF) in an all-fiber configuration, with the absence of SBS. By employing a custom-designed AR-HCF with a mode-field diameter matching that of a large-mode-area panda fiber, the system achieves high coupling efficiency without the need for free-space components or fiber post-processing. The AR-HCF attains a transmission efficiency of 92%, delivering an output power of 100.3 W with a beam quality factor (M2) of 1.22. The absence of SBS is confirmed through monitoring backward light, which shows no increase in intensity. This all-fiber architecture ensures high stability, compactness and efficiency, potentially expanding the application scope of single-frequency lasers in high-precision metrology, optical communication, light detection and ranging systems, gravitational wave detection and other advanced applications.